Bio-based poly(lactide)/ethylene-co-vinyl acetate thermoplastic vulcanizates by dynamic crosslinking: structure vs. property. Issue 21 (6th March 2015) - Ma, Piming; Xu, Pengwu; Liu, Wangcheng; Zhai, Yinghao; Dong, Weifu; Zhang, Yong; Chen, Mingqing
<x xml:space="preserve">Abstract</x> The structure–property relationships of PLA/EVA-based thermoplastic vulcanizates have been investigated for the first time.